TUNA FISH PROCESSING FOR IMPROVEMENT THE ECONOMY OF FISHERMEN'S HOUSEHOLD IN FALABISAHAYA VILLAGE, MANGOLI UTARA DISTRICT - Ismail, Firdaut; Marus, Ikbal; Irfan, Muhammad; Andriani, Rovina; Muchdar, Fatma (Jurnal Abdi Insani, 2022)
The problem seen by the people of Falabisahaya Village while being fishermen is that they experience problems in marketing fish in large quantities during the harvest season for sea fish, especially tuna. This condition, of course, involves the cooperation of the fisherman/fisherman's wife to help their husband's obligations after crossing the ocean. The objectives of this service activity are: 1) increasing the knowledge, insight and skills/skills of fishermen's wives by providing fish processing-based products, for example (fish shreds), 2) providing inspiration and active preparation so that fishing couples get arrangements to strengthen independent businesses, 3) provide preparation of bundling plans and marking of fish handling goods, and provide business prepared by implementers. As one of the marine fishery products, benefits for welfare and post-collection care and the hypothesis of making marine fish-based goods. As a result of these actions, it shows an increase in the cooperation of accomplices in the implementation of catering assistance and assistance, preparation in the coastal area for the management of fishing pairs, as well as supervision of the exchange of Trading Business Permits (SIUP). Also, outreach exercise means ensuring the existence and progress of the business they will be involved in, starting from the most common ways of providing raw components, manufacturing processes, and managing finances. then at that time, this training activity opened up knowledge for fishing couples that it turns out that fish can be made into snacks, for example shredded meat which has high nutritional value (Jusniati et al., 2017). In addition to getting the knowledge of making shredded tuna from tuna, the participants were also ready to make designs of shredded fish.